Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
A. 4x + 9 = 34
- 9 - 9
4x = 25
4 4
x = 6.25
B. (x - 4)(x + 2) = 0
x - 4 = 0 U x + 2 = 0
+ 4 + 4 - 2 - 2
x = 4 x = -2
C. 2x² - 6x + 4 = 0
2(x²) - 2(3x) + 2(2) = 0
2(x² - 3x + 2) = 0
2 2
x² - 3x + 2 = 0
x = -(-3) +/- √((-3)² - 4(1)(2))
2(1)
x = 3 +/- √(9 - 8)
2
x = 3 +/- √(1)
2
x = 3 +/- 1
2
x = 3 + 1 U x = 3 - 1
2 2
x = 4 x = 2
2 2
x = 2 x = 1
- 9 - 9
4x = 25
4 4
x = 6.25
B. (x - 4)(x + 2) = 0
x - 4 = 0 U x + 2 = 0
+ 4 + 4 - 2 - 2
x = 4 x = -2
C. 2x² - 6x + 4 = 0
2(x²) - 2(3x) + 2(2) = 0
2(x² - 3x + 2) = 0
2 2
x² - 3x + 2 = 0
x = -(-3) +/- √((-3)² - 4(1)(2))
2(1)
x = 3 +/- √(9 - 8)
2
x = 3 +/- √(1)
2
x = 3 +/- 1
2
x = 3 + 1 U x = 3 - 1
2 2
x = 4 x = 2
2 2
x = 2 x = 1
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.